Regulation of Notch Ligands Dll1 and Jag1 by Pax6 during cortical development - Dorà, Elena Ferrari (The University of Edinburgh, 2016)
The regulation of gene expression resulting in the formation of the mammalian cerebral cortex is tightly regulated by a group of transcription factors. The deletion of any one of these transcription factors results in numerous defects whose nature and severity depends on the role of the transcription factor in the regulation of complex gene regulatory networks involved in development. There is currently relatively little knowledge about the gene networks that these transcription factors control and how they exert their regulatory effects. The paired-box transcription factor Pax6 has been identified as a master regulator of gene networks involved in cortical development and its deletion results in numerous cortical defects such as an abnormally thin cortical plate and a vastly expanded proliferative zone. Previous work in our lab identified a list of candidate genes that are likely to be regulated by Pax6 in the developing cortex. Members of the Notch signalling pathway were potential Pax6 targets of particular interest since Notch signalling plays a crucial role in the maintenance of neural progenitor cells during development and consequently plays a critical role during corticogenesis. Our work aims to identify the regulatory relationship between Pax6 and Notch ligands Dll1 and Jag1 during cortical development. Analysis by flow cytometry and double labelling analysis of both gene and protein expression has provided insight into the relationship between Pax6 and Dll1 in progenitor cell subpopulations during cortical development. In situ hybridisation and qPCR results confirmed that loss of Pax6 causes loss of Dll1 expressing cells and downregulation of Jag1, indicating that both ligands are regulated by Pax6. Bioinformatic screening and analysis by luciferase assay suggests that Jag1 is a likely candidate to be a direct target of Pax6.
Keywords: notch; Pax6; cortex; Dll1; Jag1